2018
DOI: 10.5539/ies.v11n11p23
|View full text |Cite
|
Sign up to set email alerts
|

STEAM-GAAR Field Learning Model to Enhance Grit

Abstract: The STEAM-GAAR Field Learning Model to Enhance Grit is a learning model using STEAM education (Science, Technology, Engineering, Art and Mathematics) integrated with gamification (G), animation (A), augmented reality (AR) and space utilization (Field) to promote the factors that enhance a learner's grit. The purpose of this research is to: (1) synthesize a STEAM-GAAR Field Learning Model to Enhance Grit; (2) evaluate the STEAM-GAAR Field Learning Model to Enhance Grit. The sample is made up of ten specialists-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The study's inclusion of creative thinking, critical thinking, and innovative skills as an output from a well-developed VLCE used in STEAM education was well supported in the literature from around the world (Choolarb et al, 2019;Chujitarom, 2020;Chujitarom & Piriyasurawong, 2018;Ding, 2019;Jantakoon et al, 2019;Kankaew & Wannapiroon, 2019;Perignat & Katz-Buonincontro, 2019;Ruangvanich & Nilsook, 2018;Santosa et al, 2020;Sayavaranont & Piriyasurawong, 2019).…”
Section: Creative Critical Thinking and Innovation Skillsmentioning
confidence: 89%
See 1 more Smart Citation
“…The study's inclusion of creative thinking, critical thinking, and innovative skills as an output from a well-developed VLCE used in STEAM education was well supported in the literature from around the world (Choolarb et al, 2019;Chujitarom, 2020;Chujitarom & Piriyasurawong, 2018;Ding, 2019;Jantakoon et al, 2019;Kankaew & Wannapiroon, 2019;Perignat & Katz-Buonincontro, 2019;Ruangvanich & Nilsook, 2018;Santosa et al, 2020;Sayavaranont & Piriyasurawong, 2019).…”
Section: Creative Critical Thinking and Innovation Skillsmentioning
confidence: 89%
“…This allows students to connect their knowledge with their real-life (Patterson & Muna, 2019 ). In Thailand, Chujitarom and Piriyasurawong ( 2018 ) examined gamification’s use in STEAM education and reported that games are becoming more critical in Thai education. Moreover, gamification is a process that allows students to participate in learning.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…It also encourages the use of technology (e.g., gamification, animation, AR, and VR) to facilitate STEAM education. In Thailand, STEAM has been reported to offer practical help in the lives and learning of Thai students [35].…”
Section: Steam Educationmentioning
confidence: 99%
“…The AR/VR/MR enhanced projects incorporated various settings to motivate and engage students, including competitions or game components to create open challenges (Birt & Cowling, 2017; Jailungka et al, 2020; Karageorgiou et al, 2019), workshops focused on the development of AR game prototypes (Jesionkowska et al, 2020), and the design of 3D and 4D models (Kritsis et al, 2018; Park, 2014). The projects adopted different foci with some targeting the development of technical, artistic and 21st‐century skills (Chujitarom & Piriyasurawong, 2019; Jesionkowska et al, 2020) and others being more content specific such as the study by Wang, Lu and Wang et al (2018) that focused on calcium molecules and the study by Karageorgiou et al (2019) that focused on art history. One study (Park, 2014) focused on raising students' awareness about IT‐related STEAM careers through utilization of virtual reality.…”
Section: Resultsmentioning
confidence: 99%